Two of a kind: The Cerium(III) Oxidomolybdates(VI) Ce 2 Mo 3 O 12 and Ce 4 Mo 7 O 27 - Knies, Benjamin; Strobel, Sabine; Hartenbach, Ingo (Zeitschrift für anorganische und allgemeine Chemie (1950), 2025)
Although primarily received as by‐products, the title compounds can be synthesized directly by the admixture of CeO 2 , Ce, and MoO 3 , with the latter used as reactant and fluxing agent in flux‐mediated solid‐state syntheses at 850 °C for 7 days. Both cerium molybdates crystallize in space group C 2/ c with a = 1692.12(3), b = 1184.26(3), c = 1598.66(3) pm, and β = 108.4940(10)° ( Z = 12) for Ce 2 Mo 3 O 12 and a = 4609.00(12), b = 747.700(10), c = 1432.71(4) pm, and β = 101.023(2)° ( Z = 8) for Ce 4 Mo 7 O 27 . The crystal structure of Ce 2 Mo 3 O 12 comprises three crystallographically distinguishable Ce 3+ cations with coordination numbers of 8 in shapes of trigonal dodecahedra. The five different Mo 6+ cations are situated in the centers of noncondensed [MoO 4 ] 2− tetrahedra, and the overall arrangement of the mentioned building blocks is derived from the scheelite type. In the structure of Ce 4 Mo 7 O 27 , four crystallographically different Ce 3+ cations with coordination numbers of 8 and 9 are found, as well as five non‐condensed [MoO 4 ] 2− tetrahedra and one pyroanionic [Mo 2 O 7 ] 2− unit.